Looking Beyond the Euro Area Sovereign Debt Crisis - Dailami, Mansoor (World Bank, Washington, DC, 2012)
Three years into the euro area sovereign debt crisis, investors continue to shun periphery government bonds, European banks are under severe funding pressures in both the dollar and euro private term markets, and the euro area is facing an anemic growth outlook. On the face of it, the scenario portends gloom. But upon closer examination of the inner workings of the European Union (EU) governance system, the ongoing adjustment in the banking sector, and the rewiring of the landscape of euro sovereign debt markets, the future scenario looks more balanced, particularly following the conclusion of the protracted negotiations on Greek bond exchanges under an EU-backed voluntary private sector involvement (PSI) scheme. As euro area leaders formulate significant structural reforms to deal with the continent's longstanding fiscal and governance shortcomings, this note argues that striking a balance between market disciplines and centralized rule-making is the best way forward.